ON NETNOGRAPHY: DIGITAL PROMOTION TO BUILD RELIGION MODERATION IN INDONESIA - Puspita, Rosana Eri; Jayanthi, Ria; Satria, Oga (Harmoni, 2023)
The digital world is constantly evolving, and online promotion of religious moderation is a strategy that must be pursued. Habib Jafar is an influencer who actively promotes religious moderation in online media. This study analyzes netizens’ attitudes towards tolerance between Islam and other religions or belief groups in Indonesia. The research method used is qualitative with a netnographic approach. The content samples were selected by purposive sampling, and six videos were selected to observe netizens’ attitudes towards Buddhism, Hinduism, Coptic Christianity, Orthodoxy, Taoism, and Kebatinan sects, minorities in Indonesia. The sample size used was 4,376 netizen comments extracted with NAWALA software. Data is processed with NVIVO software. The data analysis results show that two things must be considered in making digital marketing concepts, namely content and influencers. Content must have helpful information and attract netizen attention. At the same time, influencers must have enabled enticing and enriching. The novelty offered in this study is a netnographic study on religion moderation research between religious people and believers in Indonesia.